PENGGUNAAN CLASSROOM LANGUAGE DALAM PEMBELAJARAN BAHASA INGGRIS BAGI GURU SDN 01 SURUH TASIKMADU KARANGANYAR - Widyahening, Ch.Evy Tri & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2018)
The aim of teaching and learning English in Elementary School is that the students can understand about the language skills well and of how they should parctice those skills in daily activities. It is hoped that they can communicate orally and writtenly in English. This article peels up the use of classroom language training in learning English for elementary school teachers of SDN 01 Suruh Tasikmadu Karanganyar. By giving explanation of classroom language and practicing it, it is hoped that it could improve the teachers’ skill in using classroom language and they could manage the class well. Beside that, teachers could also get new ideas to implement it for their students in teaching and learning process by using interesting learning media or learning method. The method used in this activity was giving information about the use of classroom language, modelling and practicing it. The result showed that all participants (teachers) became more enthusiastic, motivated, and fun when they followed this activity. It showed the active classroom atmosphere and most of them were ready to implement classroom language in teaching and learning process continuously. Classroom language is a good way to overcome students’ problems in learning English and teachers should use it because it can be one of good solution to solve students’ problems in learning English.Key words: Classroom Language, Learning English